Optimalisasi Tugas Pokok Dan Fungsi Dosen Dan Tenaga Kependidikan Pada Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Musamus - Andri Irawan; syahruddin; santi anwar (Kreativasi : Journal of Community Empowerment, 2023)
Understanding the lecturer’s and educational staff's main tasks and functions is necessary. Because tertiary institutions as providers of higher education must appear as leaders who can be relied upon in the development of progress and civilization of the nation. This service aims to make guidelines for the duties and functions of lecturers and educational staff at the Faculty of Social and Political Sciences, Musamus University, and socialize them. stages of activity namely; (1) search for literature; (2) Carry out Focus Group Discussion (FGD); (3) Design a Manual; (4) Conduct socialization related to the Manual of Main Duties and Functions for Lecturers and Education Staff at FISIP Musamus University; (5) Evaluation of activity results. From the results of the evaluation, it can be concluded that the guidelines for the Main Duties and Functions of Lecturers and Education Personnel benefit participants with a percentage level of 80% who understand and know about their respective main tasks and functions.